Long term supply elasticities: a case study for Finland - Kettunen, Lauri (Agricultural and Food Science, 1984)
Long term supply elasticities for basic agricultural products are needed for forecasting and planning of agricultural production. Despite many econometric studies on supply elasticities in Finland, so far no coherent analysis covering all products has been made. This shortcoming is the background for this study. Ordinary least squares were first used to estimate the elasticities, but since the residuals were in many cases autocorrelated, autoregressive models were also applied. The fit of the models did not improve much, but the autocorrelation disappeared, particularly when second order models were estimated. The long term supply elasticities seem to be small in general, a fact which also corresponds to expectations and earlier studies. The estimation of cross elasticities was not very successful and only one or two variables in addition to the producer price of the product concerned, could be included in the models. The estimation of supply elasticities proved to be sensitive to the inclusion of a new variable or a new observation. This may be due to the small number of observations or due to the rapid change in supply conditions which may be difficult to explain by econometric methods.